Does different repetition duration modify the post-activation performance enhancement effects? - Marçal Santos, Wesley; Rodrigues Costa, Otávio; Pereira Melo, Bruno; Pereira Guimarães, Miller; De Almeida Costa Campos, Yuri; Fernandes Da Silva, Sandro (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The post-activation performance enhancement (PAPE) is a phenomenon characterized by an acute enhancement of maximal voluntary strength, power or speed and have been used to increase acute performance in explosive activities. However, the effects of different repetition duration during the conditioning activities in PAPE have not been established yet. Aim of Study. The present study aimed to compare two different repetition duration a) Conditioning Activity Concentric (CAConc) (i.e., 1-sececcentric/ 3-sec-concentric), and b) Conditioning Activity Eccentric (CAEcce) (i.e., 3-sec-eccentric/1-sec-concentric) on subsequent countermovement jump performance. Material and Methods. Fourteen males recreationally trained participated this study. Participants alternately performed CAConc and CAEcce protocols in the leg press 45º and, after a 4-min recovery interval, performed three countermovement jumps. A 72-hour recovery interval was adopted between the protocols. Results. No significant difference in mean height and relative power of the countermovement jump among baseline and both protocols, as well as between CAConc and CAEcce (p > 0.05). However, percentage increases in mean height and relative power were observed between baseline and CAEcce (mean height: 1.36%/relative power: 2.25%), as well as between CAConc and CAEcce (mean height: 1.91%/relative power: 1.22%). Conclusions. CAEcce did not produce significant increases in the countermovement jump than CAConc, although greater percentage increases were observed for the CAEcce.
Keywords: countermovement jump; post-activation; potentiation; concentric action; conditioning; activity